Conversational Analysis: Taking the Turn in Extraordinary Kids - My Brother Doesn't Share His Girlfriend - Ricky, Ricky; Afriana, Afriana (PROJECT (Professional Journal of English Education), 2025)
This study examines taking the turn strategies within the TV program The Extraordinary Kids: My Brother Doesn’t Share His Girlfriend hosted by Steve Harvey, employing Stenström’s framework of conversation analysis. The researchers use a qualitative research method, the analysis focuses on three primary strategies: starting up, taking over, and interrupting. The findings indicate that starting up is the most frequent strategy, occurring 5 times, showcasing its role in initiating new conversational directions and maintaining the flow of interaction. Taking over occurs 3 times, reflecting moments of conversational dominance or redirection, while interrupting occurs 2 times, highlighting disruptions and shifts in conversational dynamics. This study emphasizes the importance of turn-taking in managing dialogue and maintaining engagement, providing insights into conversational patterns in media contexts. These findings contribute to the broader understanding of discourse analysis and conversational strategies, particularly in structured yet spontaneous interactions on television.